Field likeable candidates to win general elections` - New Sabah Times English, (KK) (New Sabah Times English (KK), 2017)
SUNGAI PETANI: In facing the 14th general election, Kedah UMNO and Barisan Nasional (BN) need to get out of their comfort zone by fielding candidates favoured by the people if they want to continue helming the state.